Peranan metode kerja kelompok dalam usaha meningkatkan prestasi belajar siswa bidang studi PKn di SMP Patria Bantul - Dewi, Eva Rusdiana Tunggal; Kurnia, Heri (Universitas Cokroaminoto Yogyakarta, 2021)
This study aims to obtain an overview of the use of group work methods in the civics learning process at Patria Bantul Junior High School; and to obtain an overview of the influence of group work methods on student learning achievement at Patria Bantul Junior High School. The basic assumption of this study is that the group work method is a way of presenting lessons by the way students do something (assignments) in a group area under the guidance of the teacher. Through this method, students are taught how to do assignments in groups, so that their learning achievements will be more evenly distributed. This research method uses quantitative descriptive methods. The study sample was 103 students of Patria Bantul Junior High School. Data were collected through observation, interviews, questionnaires, documentation, and literature studies. Data analysis is carried out by means of quantitative data analysis with a percentage statistics approach. The results showed that the group work method has been used in Patria Bantul Junior High School, especially Civics. The use of these methods is adapted to certain topics in civics subjects. The learning achievement score of students who use the group work method is on average 75,38 greater than the learning achievement score of students who do not use the group work method on average 60,41. The peeranan of the group work method in each civics teaching and learning process at Patria Bantul Junior High School has an effect on increasing student learning achievement. Because, the learning results show better. The conclusion is that the group work method plays a role in improving student learning achievement in the PKn field of study.